Human Resource Management, Technology Adaptation, and Environmental Policy: A Multi-Variable Study of MSME Entrepreneurship in Indonesia - Reni, Andi; Sihite, Mislan; Rijal, Syamsu (IJBLE Scientific Publications Community Inc., 2024)
This research explores the dynamics of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on the interplay between Human Resource Management (HRM), Technology Adaptation, Environmental Policy, and MSME entrepreneurship. Despite government support and encouragement, MSMEs face challenges, particularly in managing human resources effectively and adapting to technological advancements. The study investigates the impact of HRM practices, technology adaptation, and environmental policy on MSME success through the lens of entrepreneurship. Using quantitative research design and Structural Equation Modeling (SEM), the study analyzes data collected from a diverse sample of Indonesian MSMEs. The findings highlight the positive influence of effective HRM practices, technology adaptation, and environmental policy compliance on MSME entrepreneurship and success. The implications of the study suggest strategic considerations for entrepreneurs, policymakers, and stakeholders to enhance the growth and sustainability of MSMEs in Indonesia.